Prevalence and socio-demographic associations of diet and physical activity risk-factors for cardiovascular disease in Bo, Sierra Leone - Tahir Bockarie; Maria Lisa Odland; Haja Wurie; Rashid Ansumana; Joseph Lamin; Miles Witham; Oyinlola Oyebode; Justine Davies (BMC, 2021)
Abstract Background Little is known about modifiable dietary and physical activity risk factors for cardiovascular diseases (CVDs) in Sierra Leone. This information is critical to the development of health improvement interventions to reduce the prevalence of these diseases. This cross-sectional study investigated the prevalence and socio-demographic correlates of dietary and physical activity risk behaviours amongst adults in Bo District, Sierra Leone. Methods Adults aged 40+ were recruited from 10 urban and 30 rural sub-districts in Bo. We examined risk factors including: ≤150 min of moderate or vigorous-intensity physical activity (MVPA) weekly, physical inactivity for ≥3 h daily, ≤5 daily portions of fruit and vegetables, and salt consumption (during cooking, at the table, and in salty snacks). We used logistic regression to investigate the relationship between these outcomes and participants' socio-demographic characteristics. Results 1978 eligible participants (39.1% urban, 55.6% female) were included in the study. The prevalence of behavioural risk factors was 83.6% for ≤5 daily portions of fruit and vegetables; 41.4 and 91.6% for adding salt at the table or during cooking, respectively and 31.1% for eating salty snacks; 26.1% for MVPA ≤150 min weekly, and 45.6% for being physically inactive ≥3 h daily. Most MVPA was accrued at work (nearly 24 h weekly). Multivariable analysis showed that urban individuals were more likely than rural individuals to consume ≤5 daily portions of fruit and vegetables (Odds Ratio (OR) 1.09, 95% Confidence Interval (1.04-1.15)), add salt at the Table (OR 1.88 (1.82-1.94)), eat salty snacks (OR 2.00 (1.94-2.07)), and do MVPA ≤150 min weekly (OR 1.16 (1.12-1.21)). Male individuals were more likely to add salt at the Table (OR 1.23 (1.20-1.27)) or consume salty snacks (OR 1.35 (1.31-1.40)) than female individuals but were less likely to report the other behavioural risk-factors examined. Generally, people in lower wealth quintiles had lower odds of each risk factor than those in the higher wealth quintiles. Conclusion Dietary risk factors for CVD are highly prevalent, particularly among urban residents, of Bo District, Sierra Leone. Our findings highlight that forthcoming policies in Sierra Leone need to consider modifiable risk factors for CVD in the context of urbanisation.